2016
DOI: 10.13189/ujer.2016.040823
|View full text |Cite
|
Sign up to set email alerts
|

Popular Culture, English Out-of-class Activities, and Learner Autonomy among Highly Proficient Secondary Students in Hong Kong

Abstract: This paper reports on how and why proficient learners of English in Hong Kong participated in popular culture, out-of-class activities, with an emphasis on their development of learner autonomy. Autonomy in language learning is defined as an individual's ability and responsibility to take charge of his or her own learning [1]. Out-of-class learning plays an important role in language learning and learner autonomy [2]. However, to most Hong Kong students, opportunities to learn English outside of classroom may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Without the sense of being judged, the participants are able to lower their anxiety. In general, the participants reported that movies as a learning tool is more relaxing which is concurrent with the findings of other previous studies (Chan, 2016;Inage et al, 2013;Lin, 2008). Krashen (1982) mentioned that learners with low anxiety are more receptive towards language input.…”
Section: Anxietysupporting
confidence: 89%
See 2 more Smart Citations
“…Without the sense of being judged, the participants are able to lower their anxiety. In general, the participants reported that movies as a learning tool is more relaxing which is concurrent with the findings of other previous studies (Chan, 2016;Inage et al, 2013;Lin, 2008). Krashen (1982) mentioned that learners with low anxiety are more receptive towards language input.…”
Section: Anxietysupporting
confidence: 89%
“…Benson (2001) Studies on out-of-class activities produced several recurring activities that learners do in order to improve their language skill. One of the most common is the use of internet, particularly Web 2.0 applications (Chan, 2016;Che Wan et al, 2014), video call (Correa, 2014) as well as smartphones (Ncube & Suleman, 2014;Kurtz, 2012). Apart from the internet, the use of gaming as a language learning tool has also been observed in several studies (Bytheway, 2015;Piirainen-Marsh & Tainio, 2009;Miller & Hegelheimer, 2006).…”
Section: The Effects Of English Movies Towards Language Learning Processmentioning
confidence: 99%
See 1 more Smart Citation
“…With reference to Dörnyei, & Ryan (2015) who asserted that second language learners attainment relies on the students' own active and creative participation in the strategies or tech-niques used during the learning process. In this context, Chan (2016) has identified that learning outside the classroom promotes better learning performance as well as opportunity to be engaged in a fruitful academic. Mohamed Amin Embi et al (2001) and Javid, C. et.…”
Section: Definitions Of Language Learning Strategiesmentioning
confidence: 99%
“…Bialystock (1981) conducted a study investigating the factors that contributed to learners' language proficiency and concluded that OCLL, especially in communicative situations, in the target language were helpful for the development of learners' language skills and enabled learners to carry out the language tasks successfully. Chan (2016) carried out a study in order to explore how students can use popular culture and out-of-class learning to contribute to their language learning. As a result of the study, it was revealed that OCLL and proficiency were interrelated and participants primarily did self-initiated and interest-driven out-of-class learning and so increased their school performance.…”
Section: Introductionmentioning
confidence: 99%